Pengaruh Ukuran Partikel Terhadap Kerja Reaktor Bubble Fluidized Bed Gasifire - Tri Cahyanyo, Wahyu (2016)
This study aims to determine the effect of beta particle size of the bubble fluidized bed reactor working gasifire, to determine the temperature of the reactor, to determine the length of boiling water, to determine the thermal efficiency of the reactor. In this study, using a variation of the silica sand size of 0.36 mm, 0.46 mm, 0.55 mm. Retrieving data using 5 kg of rice and 10kg of silica sand include minimum speed of fluidization, reactor temperature, temperature hotspots, temperature boiled water to boil 2 liters of water every 2 minutes. The results showed a variation of 0.36 mm silica sand combustion temperature obtained the highest average for 307,50C, time effective flame for 90 minutes. old boiling water for 22 minutes and the reactor thermal efficiency of 9.81%. Variations in the size of 0.46 mm silica sand combustion temperature obtained the highest average of 1350C, effective burning time for 110 minutes. old boiling water for 52 minutes and the reactor thermal efficiency of 11.04%. Variations in the size of 0.46 mm silica sand combustion temperature obtained the highest average for 169,50C, time effective flame for 112 minutes. old boiling water for 40 minutes and the reactor thermal efficiency of 9.68%.